Interseções, aproximações e distanciamentos entre a Estratégia Saúde da Família e o Programa Bolsa Família a partir da lógica da intersetorialidade - França, Merilin Carneiro de (2014)
Health policies and Welfare in Brazil were ratified as a universal and selective, respectively, and for their efforts to achieve effective results, simultaneous cooperation of other policies is essential. Recognizing their indispensability, we propose to study (through the documentary and bibliographic research) and has set the intersectoral between these policies from the analysis of the Bolsa Família Program (PBF) and the Family Health Program (PSF), which later assumed the naming of the Family Health Strategy (ESF). Focusing on studying the mechanisms for intersectoral coordination between them. Our goal is to identify these mechanisms present in the contribution of legislation such programs, seen in the legislation the intersections between the ESF and the PBF, critically analyze the differences and intersectoral approaches between them. With this study we realize that the laws and normative documents highlight the need for intersectoral joints, but that alone is not enough. We found that these intersectoral mechanisms flagged by the documents leave gaps and suggest that these are solved by professionals and planned locally. In addition, the planning of these initiatives is at the mercy of the political will of managers and little power to enforce the collective bodies. Even with this realization that at the municipal level intersectoral proposals can be implemented in the literature shows that very few successful experiences, since there are political disputes that hinder the support at the state and federal levels to municipalities as well as at the state level towards municipalities and the Union. We stress that the principle of decentralization got a better development, PBF and ESF not managed to consolidate seen recenter the power that imposed measures adjust- which undermined the power of decision of the municipal and state health departments and social assistance. Contradictions about intersectionality observed in official documents are a constant. In addition, there omission of key policy for health, such as housing and transportation. Such situations reflect the tract reductionist and minimizing the Brazilian social policy. We can conclude that management tools such as shared planning between different policies, shared information systems, shared goals, encouraging the approximation of officials from different policies for implementation of interconnected tasks, provision for intersectoral teams, common agenda, meetings, forums and conferences intersectoral tend not to appear in the documents establishing the ESF and the PBF or appear as initiatives to meet the PBF conditionalities. The adoption of such instruments requires political will and social pressure to achieve the fact that policies meet in full, the right to health and assistance to citizens who need it.